Determining the burden of tuberculosis in Eritrea: a new approach - Mineab Sebhatu; Bahlbi Kiflom; Melles Seyoum; Nuredin Kassim; Tesfazion Negash; Andeberhan Tesfazion; Martien W Borgdorff; Marieke J van der Werf (The World Health Organization, 2007)
OBJECTIVE: To obtain an estimate of the prevalence of new cases of smear-positive tuberculosis in Eritrea using a new low-cost approach. METHODS: The study was designed to include a sample of 35 000 people divided between 40 clusters. The clusters were selected by sampling proportional to population size. In each cluster, census data were obtained from eligible individuals. Individuals aged 15 years or more were questioned about cough and its duration and smoking and were asked to provide two samples of sputum (spot and morning) for examination by fluorescence microscopy. FINDINGS: A total of 38 032 individuals were included in the study. Of the 19 197 individuals aged 15 years or more, 18 152 (94.6%) provided at least one sample of sputum. Fifteen individuals fulfilled the case definition, providing a prevalence of new cases of smear-positive tuberculosis of 90 per 100 000 (95% confidence interval, CI, 35-145 per 100 000) individuals aged 15 years or more and 50 per 100 000 (95% CI, 19-80 per 100 000) in the total population. CONCLUSION: The estimated prevalence of new cases of smear-positive tuberculosis obtained from our study is considerably lower than the estimate published by the World Health Organization. The new methodology for surveys to determine the prevalence of tuberculosis that we used is feasible in the field. This methodology should be validated in other countries and compared with other methods for measuring prevalence.